APLIKASI MOBILE LAYANAN ADMINISTRASI DESA/KELURUHAN UNTUK LAYANAN DI ERA PANDEMI COVID 19 - Yaman Khaeruzzaman; Adhi Kusnadi; Marlinda Vasty Overbeek; Moeljono Widjaja; Dennis Gunawan; Ni Made Satvika Iswari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Administrative services are a routine activity carried out by village and/or sub-district offices andallow for mobility and crowding of residents which should be avoided during the current pandemic.The administrative service procedure requires a series of approvals from the head of the RT, headof the RW, the apparatus and the head of the village/kelurahan so it takes time. Administrativeservices will be very good if they can be carried out electronically using devices that are commonlyowned by citizens such as smart cell phones so that they can be carried out faster, complying withrecommendations to avoid mobility and crowds and the slogan "stay at home" can be implemented.The stages of community service activities carried out started from needs analysis and systemdesign using the waterfall model development method. This activity will be continued at theimplementation stage so that it can be used widely for the community. The development andinstallation of village administration service applications is planned to be based on Android withcentralized data in the cloud. The system design is then verified and validated by a number of users,especially from the kelurahan because those parties are the ones who know the existing serviceprocess. The verification test states that the service process is in accordance with what is neededand the validation test states that the design is in accordance with the user's needs.